A dictionary of epidemiology - Last, John M. (Oxford University Press, 2008)
In fact, with contributions from over 220 epidemiologists and other users of epidemiology from around the globe, it is more than a dictionary: it includes explanations and comments on both core epidemiologic terms and on other scientific terms relevant to all professionals in clinical medicine and public health, as well as to professionals in the other health, life, and social sciences. Anyone seeking clarity on epidemiologic and methodological definitions important to human health will find it here. On the eve of a field trip to a foreign land, a health scientist remarked that if he had to limit his professional library to one volume on epidemiology, this would be the book he would choose